Tragedy on the comic stage - Farmer, Matthew C. (Oxford University Press, 2016)
Aristophanes' engagement with tragedy is one of the most striking features of his comedies. 'Tragedy on the Comic Stage' contextualizes this engagement with tragedy within Greek comedy as a genre by examining paratragedy in the fragments of Aristophanes' contemporaries and successors in the fifth and fourth centuries